2008
DOI: 10.1145/1462571.1462573
|View full text |Cite
|
Sign up to set email alerts
|

The Claremont report on database research

Abstract: In late May, 2008, a group of database researchers, architects, users and pundits met at the Claremont Resort in Berkeley, California to discuss the state of the research field and its impacts on practice. This was the seventh meeting of this sort in twenty years, and was distinguished by a broad consensus that we are at a turning point in the history of the field, due both to an explosion of data and usage scenarios, and to major shifts in computing hardware and platforms. Given these forces, we are at a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 6 publications
0
31
0
2
Order By: Relevance
“…As for power saving technologies in the field of database systems, The Claremont Report on Database Research 2005 [1], which has had a great impact on the future direction of database research, pointed out the importance of power saving in database systems. In [5], Graefe suggested that database systems should adopt energy efficiency as a metric for optimizations.…”
Section: Related Workmentioning
confidence: 99%
“…As for power saving technologies in the field of database systems, The Claremont Report on Database Research 2005 [1], which has had a great impact on the future direction of database research, pointed out the importance of power saving in database systems. In [5], Graefe suggested that database systems should adopt energy efficiency as a metric for optimizations.…”
Section: Related Workmentioning
confidence: 99%
“…Relational Database Management Systems (RDBMS's) are the ultimate solution for such structured data; they provide intelligent storage, and powerful querying capabilities in applications that range from commerce to education. And, despite the fact that nonrelational solutions have popped-up in the market -such as NoSQL databases, RDBMS's still answer for the greatest market-share [1], [2]. But, although RDBMS's are wonderfully engineered for data storage, they are not adequate for visual analytics -this is the point we tackle in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Our contributions are: a process model for creating DES from GES and special-purpose languages for IE extraction task modeling for each of the experts. Our concept, which brings MDA to IE research, follows the call for finding synergies between different research areas to bring new value to database (information systems) research stated in the claremont report (Agrawal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%